2021
DOI: 10.1186/s40337-021-00445-1
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of enteral feeding by nasogastric tube in young people with eating disorders

Abstract: Background Adolescents with severe restrictive eating disorders often require enteral feeding to provide lifesaving treatment. Nasogastric feeding (NG) is a method of enteral nutrition often used in inpatient settings to treat medical instability, to supplement poor oral intake or to increase nutritional intake. This systematic review sets out to describe current practice of NG in young people with eating disorders. Methods A system… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…In contrast to our results, some researchers have found a shorter LOS in NGF-treated patients [ 21 , 22 , 23 , 24 , 25 ]. In particular, one study showed that OF requires a longer period for weight restoration due to the lower caloric component (50.9 days in cases of OF vs. 33.8 days in cases of NGF) [ 22 ]; Golden et al showed that the LOS was significantly shorter in the NGF group (13.0 ± 7.3 days vs. 16.6 ± 9.0 days; p < 0.0001) [ 23 ]; faster weight restoration was described in a prospective study by Garber et al [ 15 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to our results, some researchers have found a shorter LOS in NGF-treated patients [ 21 , 22 , 23 , 24 , 25 ]. In particular, one study showed that OF requires a longer period for weight restoration due to the lower caloric component (50.9 days in cases of OF vs. 33.8 days in cases of NGF) [ 22 ]; Golden et al showed that the LOS was significantly shorter in the NGF group (13.0 ± 7.3 days vs. 16.6 ± 9.0 days; p < 0.0001) [ 23 ]; faster weight restoration was described in a prospective study by Garber et al [ 15 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the literature lacks guidance on the most appropriate mode of NGF administration (bolus, overnight regimen or continuous). A direct comparison between these three different regimens has not yet been performed [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nasogastric tube feeding has been shown to be safe and feasible in young people with an eating disorder who have consented to treatment (Hindley et al 2021). On children's wards, nasogastric tube feeds, which may be used for a range of conditions, are commonly administered enterally either through pump feeding or gravity feeding.…”
Section: Administrationmentioning
confidence: 99%
“…Nasogastric refeeding, otherwise referred to as enteral feeding, has been suggested as a lifesaving treatment when patients are physically unwell. 6 Nasogastric feeding involves insertion of a fine bore tube being passed via the nasal passage and into the stomach to provide nutrition. 7 Provision of nasogastric feeding can be delivered in different ways, either as a large bolus via gravity feeding or via a pump, continuously over a 24‐h period via a pump or provided intermittently overnight to supplement daytime oral intake.…”
Section: Introductionmentioning
confidence: 99%
“…7 Provision of nasogastric feeding can be delivered in different ways, either as a large bolus via gravity feeding or via a pump, continuously over a 24‐h period via a pump or provided intermittently overnight to supplement daytime oral intake. 6 Oral refeeding, otherwise known as meal‐based feeding, is where energy intake is provided via oral intake alone without the use of a nasogastric tube.…”
Section: Introductionmentioning
confidence: 99%